THE EFFECTIVENESS OF THE COMBINATION OF BREAKWATER AND TRENCH IN REDUCING WAVES - Afdal Abidin, Muh.
In this research, we investigate wave attenuation by a trench or breakwater through a mathematical model using 1D Shallow Water Equations. We apply two numerical schemes, namely Leapfrog and Lax-Wendroff, to solve the model numerically. We also derive the analytical solution to obtain the wave transmission coefficient. The constructed analytical solution provides an essential benchmark for validating numerical solutions. Both numerical schemes meet the required conditions for consistency and stability necessary for convergence. Simulation results indicate that both methods are effective in damping waves, with incoming wave amplitudes reduced by approximately 8.3% under certain configurations. The optimal combination of breakwater and trench is achieved when the height of the breakwater and the depth of the trench increase, and the length of these structures is adjusted to achieve a low transmission coefficient (Kt). In addition to showing consistent reductions in wave amplitudes across various structural configurations, the simulation results also demonstrate that the placement of breakwater and trench positions does not significantly impact wave damping effectiveness, thus allowing for flexibility in coastal structure design.